A Search Interpretation of Male‐Female Wage Differentials - Bowlus, Audra J. (Journal of Labor Economics, 1997)
A general equilibrium search framework is used to examine the role of gender differences in labor market behavior patterns (e.g., quit rates for personal reasons) in determining gender wage differentials. For samples of high school and college graduates from the National Longitudinal Survey of Youth (NLSY), these behavioral patterns are found to be significantly different across the sexes and account for 20%–30% of the wage differentials. In particular, they play a key role in explaining the male‐female wage differential that remains after controlling for the gender composition across occupations.